Integrating values, ascribed responsibility and environmental concern to predict customers’ intention to visit green hotels: the mediating role of personal norm - Dong, Zheng; He, Chang; Hu, Tianyang; Jiang, Tianfeng (Frontiers in Psychology, 2024)
Introduction It is crucial to understand the environmental friendly behavior of tourists. The utilization of natural resources by the tourists poses a significant threat to environmental sustainability. Fostering environmental friendly practices within tourism industry will help to protect future generation. The current study will evaluate the influence of values, ascribed responsibility, environmental concern and personal norms on customers’ intention to visit green hotels. Furthermore, it will assess the mediating effect of personal norms via ascribed responsibility and environmental concern. Methods The study collected data from Data 347 customers through a questionnaire survey method. Partial least square-structural equation model (PLS-SEM) was employed for the analysis of data. Results and discussion The findings indicate that values are significant factors affecting ascribed responsibility and environmental concern. Environmental concern direct impact on intention was insignificant. However, the environmental concern significantly affect intention to visit green hotels via personal norms indicating full mediating impact of personal norms.